PENGEMBANGAN TES DIAGNOSTIK HUKUM NEWTON BERBENTUK FOUR-TIER MULTIPLE CHOICE UNTUK PESERTA DIDIK SMA/MA SINGKAWANG - Devi Hardiyanti; Haratua Tiur Maria Silitonga; Diah Mahmuda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to developed the four-tier multiple choices diagnostic test of Newton’s law for senior high school students in Singkawang. The  method of research was developed from  Borg and Gall development model which has been simplified into 7 steps,  that were colecting data, planning, designing product, testing in a small scale, revisi, testing in a large scale and revisi final product. The test consist of 15 multiple choice questions which had 4 levels. This test involved 29 students in small scale trials and 181 students in large scale trial. Based on data analyze, four-tier multiple choices diagnostic test developed is proper to used which test caracteristic of high validity level, high reability, low moderate level of difficulty and readability index greater or equal to 5,66. The analysis results of contens validity was 0.83, item validity was 13 question valid, the reability was 0.619, 12 questions was in low moderate level of difficulty, and readability index was 6.71. Student’s response in this test was 85%. So, there were 11 of 15 four-tier multiple choices diagnostic test that could be used for revealed student’s misconception.  Keywords: Development Of Four Tier Diagnostic Multiple Choice, Newton’s Law, Test Characteristics .